Ethylene sensitivity regulates the wounding response in wild type and never ripe tomatoes. Issue 6 (2nd November 2017) - Natalini, A.; Martinez-Diaz, V.; Ferrante, A.; Pardossi, A.
ABSTRACT: Tomatoes are important sources of vitamins, minerals, and bioactive molecules. The fresh cut industry is interested in including tomatoes among the fresh cut vegetables. The wounds usually induce tissue degradation and release of juice, which can negatively affect quality during storage. The aim of this work was to investigate the role of ethylene in the processed vegetables using the never ripe (Nr) mutant and wild type tomatoes. The ethylene accumulation affected shelf life and quality based on the differential sensitivity of the genotypes to ethylene. Physiological and biochemical parameters related to membrane stability, phospholipases activities, ethylene and carbon dioxide accumulation were investigated in Nr mutant and wild type tomatoes as processed products and whole fruits. Results indicate that ethylene biosynthesis significantly regulates membrane breakdown. Nr tomatoes showed higher membrane stability, higher tolerance to wounding, and lower variability of physiological and biochemical parameters. Hence, this genotype can represent a genetic source of traits that can be exploited in fresh-cut tomato breeding programmes.